Clinical outcomes following selective laser trabeculoplasty in Afro-Caribbean patients with glaucoma at high risk for progression. Issue 9 (9th April 2021) - Realini, Tony; Shillingford-Ricketts, Hazel; Burt, Darra; Balasubramani, Goundappa K
Abstract : Aim: To characterise clinical outcomes following selective laser trabeculoplasty (SLT) in eyes of Afro-Caribbean patients with open-angle glaucoma (OAG) at high risk for progression. Methods: In a prospective interventional case series, patients meeting high-risk criteria (advanced disease, unilateral glaucoma blindness, inadequate intraocular pressure (IOP) on > 2 medications, recent progression on medications, inability to administer, afford or tolerate medications) underwent bilateral 360° SLT and managed based on their subsequent clinical course. Patient-specific indications for SLT—IOP reduction (IOP group) or reduced reliance on medical therapy (MED group)—were recorded before treatment. IOP and medication use were recorded every 3–4 months through up to 24 months of follow-up. Outcomes were analysed separately in the IOP and MED groups. Results: Among 33 right eyes (left eye outcomes were similar) in the IOP group, mean (SD) IOP was significantly reduced from 21.7 (7.5) mm Hg to 16.2–17.1 mm Hg over follow-up (p< 0.0177); medication use remained unchanged (p>0.05) at all time points. Among 36 right eyes in the MED group, mean medication use was 1.9 (0.9) at baseline and ranged from 1.2 to 1.4 medications per eye through follow-up (p< 0.0033), and mean IOP was significantly reduced at months 1–6 (to 13.1 (2.3) mm Hg, p=0.0013), months 13–18 (to 14.3 (2.8), p=0.0136) and unchanged at other time points. No vision-threatening adverse events occurred. Conclusions: Afro-Caribbean patients with OAG at risk for progression can achieve clinically and statistically significant reductions in IOP or medications through up to 24 months following a single 360° SLT treatment. Trial registration number: NCT02375009 .